Development of an electrochemical immunosensor for direct detection of acrylamide in food samples / Lau Pei Ying - Lau , Pei Ying (2020)
Acrylamide, a potential carcinogen which is mainly found in plant-based food such as potato chips, French fries, bread, biscuit, coffee and coco, after undergoing heating process at temperature above 120°C. The permissible maximum intake of acrylamide is 2.6 μg kg−1 of body weight per day to prevent cancer risk. Due to its neurotoxicity and carcinogenicity, a rapid detection method for acrylamide is strongly needed in food safety concern. Herein, a sample pre-treatment free electrochemical immunosensor was developed based on a displacement assay. In a displacement assay format, an antibody is initially bound to the surface immobilized hapten (analyte analogue) and upon adding of analyte (which is acrylamide in this study), antibody would exhibit a higher affinity towards its target analyte compared to hapten. This phenomenon leads to the dissociation of antibody from hapten where a displacement assay occurs. The dissociation of anti-acrylamide antibody from the electrode surface bound hapten is the predominant factor for an effective displacement assay to take place. Therefore, the objective of this study is to investigate the effect of introducing electro-pulsion to enhance the dissociation of antibody from the surface bound hapten. The displacement assay was then being analysed in a series of electro-pulsion with positive and negative charge. Other than that, pulsing potential and pulsion duration are also factors that affecting the displacement of antibody. Consequently, the optimal conditions for a displacement assay were identified via actual experimental set-up. The findings showed the dissociation rate of antibody from the surface bound hapten could be enhanced by applying a negative electro-pulsion to the working electrode surface. In addition, a three-level three-factorial Box-Behnken experimental design was employed as theoretical statistical method to confirm the optimal displacement conditions required based on a minimal experiment number (17 trials) without involving all possible experimental combinations. By pulsing the electrode with -800 mV for 10 minutes (the optimal displacement conditions), a linear dynamic range from 0.01 μg mL−1 to 35.00 μg mL−1 was obtained, with limit of detection (LOD) of 3.84 ng mL−1. The evidences of high reproducibility and repeatability of developed immunosensor by performing a satisfied relative standard deviation (RSD) of 3.13% in reproducibility test and RSD of 5.49% to 8.22% for repeatability (intra-day and inter-day) assessments. The immunosensor could retain its detection ability for 90.69% even after 28 days storage and showed high specificity toward acrylamide. The accuracy of developed immunosensor was validated by using standard method, GC−MS. Moreover, the recoveries obtained of spiked sample were ranged between 90.33% to 99.23%. As a conclusion, the developed immunosensor showed a high reproducibility, repeatability, selectivity, sensitivity, and stability for the determination of acrylamide typically in liquid food samples (coffee, coco, and prune juice). Due to its simplicity of use which exclude sample pre-treatment steps, this developed immunosensor is believed to have potential to provide a direct and quantitative approach for the detection of acrylamide.